Pengaruh Pendapatan Asli Daerah (PAD) dan Dana Perimbangan Terhadap Kinerja Keuangan Pemerintah Daerah Kabupaten dan Kota di Provinsi Kalimantan Selatan Tahun 2012-2021 - Handayani, Nur Ayu; Muzdalifah (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2024)
This research was conducted to determine the effect of Local Own Revenue and balancing funds on financial performance in terms of the ratio of operating activities and how the financial performance of local governments when viewed from the analysis of financial ratios. This study uses descriptive analysis, classical assumption test, and multiple linear regression analysis. The results of the study show that regional original income has no significant effect on financial performance, while balancing funds have a significant negative effect on financial performance. When viewed from the analysis of financial ratios, the financial performance of local governments is not good enough because most of the financial ratios still tend to be in the low category, meaning that local governments are still unable to reduce the level of dependence on financial assistance from the central government.